2001
DOI: 10.1007/s004210100499
|View full text |Cite
|
Sign up to set email alerts
|

Muscle glycogen supercompensation: absence of a gender-related difference

Abstract: Recently it has been reported that women do not have the capacity to accumulate supranormal levels of muscle glycogen when subjected to a carbohydrate (CHO) loading regimen [Tarnopolsky et al. (1995) J Appl Physiol 78:1360-1368]. Since, in this study, CHO intake relative to body mass in the female subjects was much lower than that in males, our primary aim was to re-examine this issue using subjects fed comparable amounts of CHO. Endurance-trained female and male subjects ingested 12 g CHO x kg(-1) lean body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
(65 reference statements)
3
29
2
Order By: Relevance
“…Other studies have not observed reduced muscle glycogen storage in female athletes (Walker et al, 2000;James et al, 2001). Thus, with adequate energy and carbohydrate intake, female athletes benefit from carbohydrate loading as much as male athletes.…”
Section: Carbohydrate Loading In the Days Before Exercisementioning
confidence: 99%
“…Other studies have not observed reduced muscle glycogen storage in female athletes (Walker et al, 2000;James et al, 2001). Thus, with adequate energy and carbohydrate intake, female athletes benefit from carbohydrate loading as much as male athletes.…”
Section: Carbohydrate Loading In the Days Before Exercisementioning
confidence: 99%
“…Considering that this protocol is more time consuming than that of the 3 day classical regimen (Ahlborg et al 1967;Bergstro¨m et al 1967), the protocol of Sherman and colleagues (1981) is often modified by starting the regimen with a high carbohydrate diet while ceasing or tapering-down exercise (Burke et al 2000;Rauch et al 1995). During the past decade, most studies of carbohydrate loading have used either the 3 day classical regimen or the original/modified regimen of Hickner et al 1997;James et al 2001;Madsen et al 1990;Widrick et al 1993).…”
Section: Introductionmentioning
confidence: 97%
“…Although the above-mentioned carbohydrate loading regimens can elevate muscle glycogen content to levels of 160-200 mmolAEkg -1 wet mass, they share the limitation that 2-6 days are advocated as the periods required to attain these high glycogen contents (Ahlborg et al 1967;Bergstro¨m et al 1967;Burke et al 2000;Greiwe et al 1999;Hickner et al 1997;James et al 2001;Lamb et al 1991;Madsen et al 1990;Rauch et al 1995;Sherman et al 1981;Widrick et al 1993). This is a severe limitation for athletes who may not wish to disrupt their normal training schedules over such a long period.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Since both women and men use glycogen from brain liver and muscle for fast energy during physical stress and during chess playing, mental fatigue occurs earlier in women [125,126], because their body glycogen content is lower if compared to men due to hormonal conditions [127][128][129][130][131] and chess demand for fast energy for women is equal to men. This would indeed lower speed of conflict control at an earlier time point for women during a chess game.…”
Section: Chess and Gendermentioning
confidence: 99%